Checklist of Social (Polistinae) and Solitary (Eumeninae) Wasps from a Fragment of Cerrado “Campo Sujo” in the State of Mato Grosso do Sul, Brazil - Yuri Campanholo Grandinete; Fernando Barbosa Noll (Sociobiology)
Cerrado is one of the richest biomes in the world but it is still very threatened by human actions that affect not only the flora, but also the fauna, and certainly the largest known group, the insects. We present here a list of species of Polistinae and Eumeninae wasps, based on three different methodologies in a fragment of Cerrado “campo sujo”, very affected by livestock raising, in Paranaíba, State of Mato Grosso do Sul. We recorded 22 species of Polistinae within 8 genera, with Polybia and Agelaia as the most representative. For Eumeninae, 21 species within 10 genera were recorded, with Montezumia and Pachodynerus as the most representative. Furthermore, this work shows the first records of Eumeninae in Mato Grosso do Sul and some new of Polistinae, compared to the literature.